The strategic link between innovation and MSME performance: Evidence from culinary businesses in solo Raya - Putra, Ardian Prima; Riani, Asri Laksmi; Irianto, Heru; Suwarto, Suwarto (International Journal of Innovative Research and Scientific Studies, 2025)
This quantitative study aims to test the proposed hypothesis on the mediating role of business strategy (BS) in the effects of innovation on enhancing MSME performance. Data collection employed the survey method. The multivariate data analysis shows that BS mediates the influence of innovation on the performance of MSMEs. This study involved 232 respondents from MSMEs in the culinary sector in the Greater Solo area. The results reveal that well-designed business strategies—encompassing meticulous planning, effective execution, and continuous evaluation—positively affect the enhancement of MSME performance. A focused approach not only enables MSMEs to better adapt to changes in the business environment but also strengthens their competitiveness in dynamic markets. Optimal MSME performance reflects operational success while directly impacting the sustainability and welfare of the business. These findings support previous theories that emphasize the importance of synergy between innovative business strategies and entrepreneurial behavior in enhancing operational efficiency and business competitiveness.